2018
DOI: 10.18535/ijsshi/v5i5.08
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corporate Social Responsibility on Corporate Image, Customer Satisfaction and Customer Loyalty: An Empirical Study on the Telecommunication Industry

Abstract: The government requires enterprises to have adequate corporate social responsibility (CSR) and as such must prepare CSR reports to detail the avoidance of improperly obtained profits. Selling price is no longer the sole factor of purchase behavior to ensure that customers acquire better goods and a higher quality of service. The corporate image of enterprises within an industry has become the key factor of purchase behavior. Therefore, the implementation of CSR will not only affect corporate image, but also af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Environmental issues are at the heart of customers' concerns (Eid et al. , 2020; Hsu, 2018; Han et al. , 2019), and this has been found to be relevant, which is a novelty in terms of previous research.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 88%
See 3 more Smart Citations
“…Environmental issues are at the heart of customers' concerns (Eid et al. , 2020; Hsu, 2018; Han et al. , 2019), and this has been found to be relevant, which is a novelty in terms of previous research.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 88%
“…A novelty for this scale is the item which investigates the organization's involvement in the community. Environmental issues are at the heart of customers' concerns (Eid et al, 2020;Hsu, 2018;Han et al, 2019), and this has been found to be relevant, which is a novelty in terms of previous research. The fifth dimension, perception of the service, confirms that the quality and good value of a service, along with a complete range of services, are important in corporate image formation, as stated in Nguyen (2006), Chen and Chen (2014) and Huang et al (2014).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 91%
See 2 more Smart Citations
“…G. Park et al, 2012). Cross-buying intention is the intention to consume a new product or service a mobile carrier introduces; it was measured on a seven-point scale with four questions (Hsu, 2018; Joo & Kwon, 2017; Sridhar & Mehta, 2018). Table 1 presents the measurement items and reliability of major variables, excluding the measurement items of corporate characteristics that affect reputation formation.…”
Section: Methodsmentioning
confidence: 99%